ISLAMIC LEGAL ANALYSIS OF SHARIA ECONOMIC DISPUTES REGARDING DEFAULT COMMITTED BY DEBTORS AT BANK OCBC NISP TBK, CQ. OCBC NISP SHARIA BUSINESS UNIT DURING COVID-19 ( DECISION NUMBER 2113/PDT.G/2024/PA.SBY ) - Fauziah, Nur (Journal Of Sharia Banking, 2025)
The COVID-19 pandemic has had a significant impact on various sectors, including the Islamic banking sector. One of the impacts is the increasing cases of default by debtors, especially in micro-financing channeled by institutions such as OCBC NISP Sharia Business Unit. In the context of Islamic law, default is understood as a violation of a valid contract according to sharia, but also provides leniency in emergency conditions such as a pandemic. This study aims to analyze debtor default against OCBC NISP Sharia Business Unit during COVID-19 based on an Islamic law perspective. The study uses a normative legal method with a qualitative approach through a literature study of primary, secondary, and tertiary legal sources. The results of the study show that Islamic law accommodates the principles of justice and welfare in resolving defaults, through approaches such as rescheduling, reconditioning, and restructuring. In addition, the Qur'an emphasizes the need for tolerance towards debtors who are experiencing economic difficulties. Therefore, the implementation of restructuring solutions in sharia financing during the pandemic is a form of implementing fair and civilized sharia principles.